2015
DOI: 10.11648/j.ajbio.20150306.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biochemical Marker - Glutathione and DNA Fingerprinting of Biofield Energy Treated <i>Oryza sativa</i>

Abstract: Abstract:Food production needs to increase to satisfy the demand due to increasing human population worldwide. To minimize this food crisis, an increase in the rice production is necessary in many countries. The current study was undertaken to evaluate the impact of Mr. Trivedi's biofield energy treatment on rice (Oryza sativa) for its growth-germination of seedling, glutathione (GSH) content in seedling and mature plants, indole acetic acid (IAA) content in shoots and roots and DNA polymorphism by random ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 37 publications
0
64
0
Order By: Relevance
“…However, the National Center for Complementary and Alternative Medicine (NCCAM), well-defined Biofield therapies in the subcategory of Energy Therapies [13]. The Trivedi Effect ® -Consciousness Energy Healing Treatment has been reported with significant revolution in the physicochemical properties of metals, chemicals, ceramics and polymers [14][15][16], improved agricultural crop yield, productivity, and quality [17,18], transformed antimicrobial characteristics [19][20][21], biotechnology [22][23], improved bioavailability [24][25][26], skin health [27,28], nutraceuticals [29,30], cancer research [31,32], and human health and wellness.…”
Section: Introductionmentioning
confidence: 99%
“…However, the National Center for Complementary and Alternative Medicine (NCCAM), well-defined Biofield therapies in the subcategory of Energy Therapies [13]. The Trivedi Effect ® -Consciousness Energy Healing Treatment has been reported with significant revolution in the physicochemical properties of metals, chemicals, ceramics and polymers [14][15][16], improved agricultural crop yield, productivity, and quality [17,18], transformed antimicrobial characteristics [19][20][21], biotechnology [22][23], improved bioavailability [24][25][26], skin health [27,28], nutraceuticals [29,30], cancer research [31,32], and human health and wellness.…”
Section: Introductionmentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23,24], nutraceuticals [25,26], organic compounds [27][28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate displays the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [19]. The Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [20], altered antimicrobial sensitivity of pathogenic microbes in microbiology [21][22][23], biotechnology [24,25], genetics [26,27], changing the structure of the atom in relation to the various metals, ceramics, polymers and chemicals materials science [28][29][30], altered physical and chemical properties of pharmaceuticals [31,32], nutraceuticals [33,34], organic compounds [35][36][37], and improved overall growth and yield of plants in agricultural science [38,39].…”
Section: Introductionmentioning
confidence: 99%